Abdominoscrotal Hydrocele: An Uncommon Cause of Abdominoscrotal Cystic Swelling - Swarnkar, Manish (Case Rep Urol, 2021)
Abdominoscrotal hydrocele (ASH) consists of fluid-filled intercommunicating inguinoscrotal and abdominal sac with a characteristic hourglass-like picture on CECT, which usually affects single testis and a rare cause of abdominoscrotal cystic swelling. The precise etiology of ASH is not known. Ultrasonography is the initial diagnostic modality of choice as it demonstrates the intercommunication between the two sacs and also identifies any abnormality of the testis and genitourinary tract. We are reporting a case of a 27-year-old patient presented in the General Surgery OPD of Acharya Vinoba Bhave Hospital in 2019 with bilateral scrotal and abdominal swelling. On examination, cross fluctuation was positive between left hydrocele and abdominal swelling, raising suspicion of ASH, which was confirmed on CECT. The patient underwent excision of sac through left inguinoscrotal approach and an uneventful postoperative course.